(untitled) (PerCursos, 2021)
This work exposes the data referring to the GDP and the GDP per capita collected by the research “Territorial governance in Brazil: institutional specificities, spatial logics and development policies”. Such data indicate inequality during the period studied (2002 – 2014) and motivate the basic question that guides this work: does inequality hinder participation in the scope of governance structures? Thus, assuming that the basic function of governance structures is to encourage cooperation and participation through the handling of conflicts, the hypothesis for the question raised can be expressed in the following statement: inequality contributes to institutional inertia and to the stability present in relationships between actors, hindering cooperation, participation and sustainable territorial development. In this case, the functioning of governance structures can be described more by inertia and less by institutional change. The general results of the research on which this work is based indicate that cooperation and participation are truncated, reinforcing the proposed interpretation. The method for analyzing the data and developing the hypothesis was based on a simplified model of reality, the game, formed by the concepts of actors and institutions.